Development and Practical Use of the New Quantitative Bleeding Time Test Apparatus - Tamai, Yoshiko; Takami, Hideki; Nakahata, Rieko; Nakui, Yuka; Akagi, Tomoaki; Munakata, Akihiro (Thrombosis and Haemostasis, 1998)
We have developed a new computerized system for measurement of quantitative bleeding time (QBT) to detect subtle abnormalities of primary hemostasis that are difficult to detect with the standard bleeding time determination. This new apparatus can simultaneously measure the bleeding time (BT; sec), amount of total blood loss (Tv; μl), maximum bleeding rate (Rmax; μl/sec) and bleeding pattern from the bleeding time incision. We have also developed a new holder for the Simplate that enables more consistent incisions and thus improves the reproducibility of the BT test.In this study, the newly developed QBT test was performed in 137 normal healthy volunteers and 10 patients having defined abnormalities of either primary or secondary hemostasis. Comparisons of the standard BT test and our QBT were made in 5 normal subjects and 7 thrombocytopenic patients. Additionally, 6 normal subjects were examined with both tests before and after administration of aspirin. Those results show that our QBT appears to be a more sensitive indicator of primary hemostasis than the standard BT method.